Islamic extremism and the war of ideas : lessons from Indonesia - Hughes, John, 1960- (Hoover Institution Press publication, 2010)
John Hughes examines lessons learned from the practice of public diplomacy, especially international broadcasting, in the cold war and tells how the United States could more effectively counter extremism, promote democracy, and improve understanding of itself in the Islamic world. He offers Indonesia as a successful example of the melding of democracy, Islam, and modernity and suggests that this country and other nations where Islam and democracy coexist, such as Turkey, could play a significant role in helping thwart Islamist extremism.